Loss Accounting Practice: Study of Islamic Ethnomethodology - Thalib, Mohamad Anwar (Journal of Islamic Economics (JoIE), 2024)
Introduction: This research departs from the problem of concepts and theories about loss accounting currently being studied and implemented, which are knowledge based on modern values. It creates an opportunity to lose local cultural values ​​from the loss of accounting practices. Research Methods: This study aims to formulate loss accounting practices based on Gorontalo Islamic cultural values. This study uses a spiritual paradigm with an Islamic ethnomethodology approach. Results: The study found three strategies of the coachmen in avoiding losses: pray to ask for sustenance from Allah, open a side business, and use the money saved to cover losses. The three accounting practices for avoiding losses are based on the value of local wisdom in the form of mopo’o tanggalo duhelo, which means full of patience. The value of patience lives on the belief that the human task is to try because the Creator has arranged sustenance. Conclusion: the concept of loss accounting based on the value of local wisdom of the Gorontalo community, which is conditional on faith in the Almighty.